Clonal Diversity of Methicillin-resistant Staphylococcus aureus in UKM Medical Centre: characterisation by Multilocus Sequence Typing of different SCCmec type representatives - Najihan Abdul Samat Muttaqillah,; Salasawati Hussin,; Hui, Min Neoh; Ainihayati Noordin,; Chuan, Hun Ding; Asrul Abdul Wahab,; Md Mostafizur Rahman, (Universiti Kebangsaan Malaysia, 2015)
Multilocus sequence typing (MLST) has been used to characterise methicillin-resistant Staphylococcus aureus (MRSA) isolates into sequence types (STs) and together with SCCmec typing, form the clonal nomenclature for MRSA. MLST was conducted as per the standard protocol on ten out of 236 isolates collected previously from January to December 2009 representing four different SCCmec types. Relationship analysis was performed with eBURST via the MLST website. Four unlinked ‘singleton’ STs were detected: ST30, ST239, ST772 and ST1178. Together with SCCmec typing, five MRSA clones were identified: ST30-IV, ST239-II, ST239-III, ST772-V and ST1178-IV. Clones ST239-III and ST30-IV are already established in Malaysian hospitals and in the local community, respectively. ST772-V is an emerging clone reported previously to have a propensity to displace pre-existing predominant clones. A clone involving the predominant ST in Malaysia (ST239) with SCCmec type II is the first of its kind to be identified. MRSA clones in our centre are very diverse and clone surveillance with large sample sizes should be undertaken as collaborative efforts between local institutions to maximise detection coverage.